(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Floods are hydrometeorological disasters have complex impacts on the social, economic, health, and housing conditions of affected communities. Post-flood conditions often force people to evacuate due to limited facilities and increased vulnerability of vulnerable groups. This Community Service (PkM) activity aims to provide humanitarian support and obtain an overview the social and housing conditions of flood-affected communities as a basis for assistance and social recovery. The method used is descriptive-participatory with direct approach the evacuation sites. Activities include collecting demographic data and housing conditions, distributing aid, and providing social assistance to affected communities. Data collection was conducted on 48 respondents voluntarily, taking into account the principles of ethics and respondent comfort. The results of the activity indicate that the majority of respondents are of productive age with lower secondary education levels and are predominantly informal workers. Most respondents experienced light to severe damage to their homes, even making them uninhabitable, requiring temporary housing support and assistance with basic needs. The community service activity also had a positive impact in the form of an increased sense of security, togetherness, and social solidarity in the evacuation areas. The discussion demonstrated that a humanistic and participatory community service approach is relevant in addressing the needs of flood-affected communities, not only in terms of short-term assistance but also in supporting social and psychosocial recovery. This activity emphasized the strategic role of higher education institutions in mitigating the impacts of flooding through community service that is applicable and oriented to the community’s real needs.